Balancing Roles: The Impact of Work-Life Integration on Female Job Satisfaction in Nepal’s Service Sector - Sharma, Santosh; Chhetri, Ashmita Dahal (Chaturbhujeshwar Academic Journal, 2025)
This study examines the impact of work-life balance (WLB) on job satisfaction among female employees within Nepal’s service sector, emphasizing five critical dimensions: welfare policy, flexible work hours, managerial support, work-family conflict, and job design. Grounded in Work-Life Border Theory and Herzberg’s Two-Factor Theory, the research utilized a quantitative methodology, surveying a sample of 233 female employees from banking, healthcare, education, hospitality, and government sectors in Chitwan, Nepal. Data were analyzed through descriptive statistics, correlation, and multiple regression analyses. Results reveal that welfare policies and managerial support have a significant positive effect on job satisfaction, whereas flexible work hours and job design show positive but statistically non-significant influences. Conversely, work-family conflict negatively correlates with job satisfaction, highlighting persistent challenges in managing work and domestic demands. The study shows that gender‐responsive practices, empathetic leadership, and culturally aware job design improve women’s well-being and organizational results.. These results offer valuable implications for policymakers, managers, and scholars committed to fostering inclusive and sustainable workplace environments in Nepal.